2013
DOI: 10.1186/cc11917
|View full text |Cite
|
Sign up to set email alerts
|

Co-enrollment of critically ill patients into multiple studies: patterns, predictors and consequences

Abstract: IntroductionResearch on co-enrollment practices and their impact are limited in the ICU setting. The objectives of this study were: 1) to describe patterns and predictors of co-enrollment of patients in a thromboprophylaxis trial, and 2) to examine the consequences of co-enrollment on clinical and trial outcomes.MethodsIn an observational analysis of an international thromboprophylaxis trial in 67 ICUs, we examined the co-enrollment of critically ill medical-surgical patients into more than one study, and exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…It is therefore essential to carefully record and monitor enrolment practices and make improvements where possible. We have successfully conducted other international trials [38–42] and are interested to evaluate co-enrolment across participating centers and countries [43]. When thoughtfully approached, co-enrolment has not been found to impact on trial results [43, 44], and thus, ways to maximize safe co-enrolment opportunities will be explored in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore essential to carefully record and monitor enrolment practices and make improvements where possible. We have successfully conducted other international trials [38–42] and are interested to evaluate co-enrolment across participating centers and countries [43]. When thoughtfully approached, co-enrolment has not been found to impact on trial results [43, 44], and thus, ways to maximize safe co-enrolment opportunities will be explored in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In addition to concerns about statistical power, increased risk of adverse events (AEs), and the interpretation of study results, there may be a problem with outcome ascertainment bias. 11 Thus, whether to allow co-enrollment in 41 clinical trial requires a careful assessment of the potential impact on the study results, interactions between the interventions, subject safety, and the scientific validity of the clinical trials. [12][13][14][15]…”
Section: Strategies To Consider When Planning For Co-enrollmentmentioning
confidence: 99%
“…Allowing coenrollment, when scientifically appropriate, respects the role of parents in deciding for their neonate and may result in a more representative population of those neonates who would receive the 2 interventions in clinical practice. 7,9,11 There are no data to indicate that it may be too stressful and thus unethical to approach parents about co-enrollment in multiple studies. 10 One study showed that most mothers of neonates were willing to participate in 41 study.…”
Section: Parental Permissionmentioning
confidence: 99%
“…In an era where the incidence, 17 mortality, 18 and management options for ALI are changing, rapid patient accrual is an important goal. Trialists, therefore, strive to implement their studies across national borders, to coenroll patients across trials where appropriate, 19 and to include the broadest case mix supported by current clinical practice and expectations for net benefit.…”
Section: Advantages Of Heterogeneous Study Populationsmentioning
confidence: 99%